Corporate Balance Sheet Restructuring and Investment in the Euro Area - Jaeger, Albert (IMF Working Papers; Working Paper ;, 2003)
The recent boom-bust cycle in the euro area's equity valuations has left nonfinancial corporations saddled with a legacy of high debt or leverage. Models of corporate investment behavior based on imperfect capital markets predict that highly leveraged balance sheets can act as a brake on investment spending. The paper's empirical analysis suggests that leverage effects on corporate investment can be substantial and persistent, particularly if leverage exceeds threshold values.